Pengurusan liabilti dalam pentadbiran harta pusaka - Md Yusof, Naziree; Ab Kadir, Nor Aida; Ahmad Bustami, Tajul Aris (Faculty of Law, Accountancy and International Relations, UniSZA, 2015)
Academic writing about the concept of estate planning commonly focuses on faraid (Islamic law of inheritance), wills, gifts, charitable assets, vows, the division of jointly acquired properties etc to make it in accordance with the current practice. This paper will discuss about constraints and problems that cause most likely the distribution of the estate among the heirs rather difficult to be distributed through the existing method. This article does not deny the significant of faraid but the negative impact from the constraints should be created a new mechanism so the rights of all the heirs would be properly secured as well as the wishes of the deceased also preserved.